The other narratives of architecture - Paramita, Kristanti Dewi (Department of Architecture Faculty of Engineering Universitas Indonesia, 2024)
The other narrative of architecture expands possibilities of architectural design methods that pay attention to other temporalities, realities, and subjects of architecture. The collection of articles in this ARSNET issue provides investigations that revisit how narratives exist as the basis of architectural experience and design methods. Technological advancements create tools, platforms, and living needs that enable different ways of revealing, producing, and speculating architectural narratives. Through this issue's investigation of the other narratives, alternative situations of architecture are reconstructed.